2010
DOI: 10.5194/acp-10-2209-2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular distributions of dicarboxylic acids, ketocarboxylic acids and α-dicarbonyls in biomass burning aerosols: implications for photochemical production and degradation in smoke layers

Abstract: Abstract. Aerosols in the size class <2.5 µm (6 daytime and 9 nighttime samples) were collected at a pasture site in Rondônia, Brazil, during the intensive biomass burning period of 16-26 September 2002 as part of the Large-Scale Biosphere-Atmosphere Experiment in Amazonia -Smoke, Aerosols, Clouds, Rainfall and Climate (LBA-SMOCC). Homologous series of dicarboxylic acids (C 2 -C 11 ) and related compounds (ketocarboxylic acids and α-dicarbonyls) were identified using gas chromatography (GC) and GC/mass spectro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
189
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(211 citation statements)
references
References 67 publications
17
189
5
Order By: Relevance
“…In case of the haze episode observed in this study, a substantial portion of the dicarboxylic acids was likely derived from atmospheric oxidation, namely, aging processes, during transport of the smoke particles to the sampling site in light of the favorable conditions. A substantial increase in water-soluble organics in smoke aerosols, including organic acids, has also been reported from previous studies in SEA and elsewhere (Agarwal et al, 2010;Graham et al, 2002;Gao et al, 2003;Kundu et al, 2010).…”
Section: Chemical Speciation Of Tspmentioning
confidence: 66%
“…In case of the haze episode observed in this study, a substantial portion of the dicarboxylic acids was likely derived from atmospheric oxidation, namely, aging processes, during transport of the smoke particles to the sampling site in light of the favorable conditions. A substantial increase in water-soluble organics in smoke aerosols, including organic acids, has also been reported from previous studies in SEA and elsewhere (Agarwal et al, 2010;Graham et al, 2002;Gao et al, 2003;Kundu et al, 2010).…”
Section: Chemical Speciation Of Tspmentioning
confidence: 66%
“…The C max was observed for heptanedioic acid in a concentration range from 0.28 mg g À1 OC (woodstove with cold start e cork oak) to 10.2 mg g À1 OC (fireplace with hot start e Holm oak). Dicarboxylic acids in the same carbon range have been detected previously in the emissions from residential wood burning (Fine et al, 2004a,b;Gonçalves et al, 2010) and from wildfires (Alves et al, , 2011Kundu et al, 2010). Average concentrations of total dicarboxylic acids in PM 2.5 samples collected during the burning season in Amazonia were 2e8 times higher than those reported in urban aerosols (Kundu et al, 2010).…”
Section: Homologous Compound Seriesmentioning
confidence: 75%
“…Dicarboxylic acids in the same carbon range have been detected previously in the emissions from residential wood burning (Fine et al, 2004a,b;Gonçalves et al, 2010) and from wildfires (Alves et al, , 2011Kundu et al, 2010). Average concentrations of total dicarboxylic acids in PM 2.5 samples collected during the burning season in Amazonia were 2e8 times higher than those reported in urban aerosols (Kundu et al, 2010). However, dicarboxylic acids are ubiquitous compounds that can be generated from several primary sources or secondary processes and, thus, cannot be regarded as biomass burning tracers.…”
Section: Homologous Compound Seriesmentioning
confidence: 86%
See 1 more Smart Citation
“…The ubiquity of di-carboxylic acids (DCA) is well documented both in urban and rural terrestrial aerosol and marine aerosol (Warneck, 2003;Tan et al, 2010;Sempéré and Kawamura, 1996;Pavuluri et al, 2010;Ma et al, 2013;Kundu et al, 2010;Kawamura et al, 1996Kawamura et al, , 2007Gierlus et al, 2012;Altieri et al, 2008). A recent study of marine aerosol from around the globe found that DCA contribute on average ∼ 15 % to total marine organic aerosol (OA) mass (Fu et al, 2013;Myriokefalitakis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%